Programming HD DVD and Blu-ray Disc : - Zink, Michael (Mcgraw-Hill, 2008)
This complete book/DVD package covers everything you need to know in order to write optical working code for HD and Blu-Ray DVD applications.This comprehensive tutorial not only teaches the new programming skills but also includes large chunks of reusable code and demonstrates actual code outcomes.